The role of individual factor in knowledge sharing behavior among profit oriented webloggers - Zakaria, Ruzleeta; Sulaiman, Nor Intan Saniah; Ibrahim, Haslinda; Abdullah, Mohd Syazwan; Zabidi, Nerda Zura (2013)
Knowledge management involves a variety of important processes such as knowledge creation, knowledge sharing and knowledge dissemination. There are two objectives that must be considered in order to achieve knowledge management processes; it is getting the right knowledge to people, thus enabling them in engaging with it and learning from it. However, it must go through the process of socialization as these involve social interactions to accomplish knowledge sharing activities. This social interaction consists of individual interactions and participation occurs when both important elements are involved, the knowledge sharing becomes effective. Knowledge sharing has been the most discussed topic and a challenge for organizations because of its importance in the success of knowledge management efforts. In general, knowledge sharing is related to an action which refers to people's behavior or actions in sharing or not sharing knowledge, donating and collecting knowledge. In this paper, the discussion about knowledge sharing relates to peoples' behavior, and this behavior must be assisted and therefore it leads to the term knowledge sharing behavior. Many researchers believed that weblogs are an innovative knowledge sharing technology. The increase use of weblogs each year has shown that weblogs are an effective social networking medium and can be extended beyond simple communication within a community. Many research studies in Malaysia are focused on knowledge sharing behavior within the organization and community. A few studies were conducted to explore knowledge sharing behavior among webloggers. However, research study that focuses on profit oriented webloggers still has not been explored in Malaysia. Thus, this paper discusses our present research that intends to explore the role of individual factor in knowledge sharing behavior among profit oriented webloggers. The paper will highlight the problems related to knowledge sharing behavior from the perspective of profit oriented webloggers and how these problems can be addressed. In addressing these problems, a few interviews will be conducted with identified webloggers. This study will adapt knowledge sharing behavior theories such as Theory of Planned Behavior, Social Cognitive Theory, Social Capital Theory and Social Exchange Theory. This will help us to understand the individual factors that can influence knowledge sharing behavior among profit oriented webloggers in Malaysia. Do you want to read the rest of this article?Request full-text